You are Here: Home >< Maths

# Solve the equation A2 watch

1. Ok, solve the equation

y²+5y - (36/y²+5y) = 0

OK, so its pretty obvious that we make t = y²+5 therefore giving us...

t - 36/t = 0

Then i multiplied through by t giving

t² - 36 = 0

Then from here I said
t²=36
obviously therefore t = √36 = 6

from here i get.... y²+5y-6 = 0 giving me the results ..
(y+1) (y-6)
y = -1 y = + 6

The question is what do i do now, i'm sure there are more answers than that?
2. (Original post by Gaz031)
Giving: y²+5y+6 = 0

(y + 3)(y + 2) = 0

y = -3, y = -2

### Related university courses

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: June 26, 2005
The home of Results and Clearing

### 2,728

people online now

### 1,567,000

students helped last year
Today on TSR

### University open days

1. Sheffield Hallam University
Tue, 21 Aug '18
2. Bournemouth University
Wed, 22 Aug '18
3. University of Buckingham
Thu, 23 Aug '18
Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams